GIS preprocessing for rapid initialization of HEC-HMS hydrological basin models using web-based data services. (August 2020) - Castro, Cyndi V.; Maidment, David R.
Abstract: Hydrological GIS preprocessing tools are used to spatially relate different datasets for producing topologically connected watersheds and deriving attributes for model parameterization. Obtaining such information requires disparate data-sources from various websites with lengthy processing requirements. This research describes the development of HMS-PrePro, an open-source GIS preprocessing tool that was developed for the U.S. Army Corps of Engineers' (USACE) Hydrologic Engineering Center's Hydraulic Modeling System (HEC-HMS) software. HMS-PrePro provides data as a service by connecting to Esri's Living Atlas web service and extracting authoritative hydrological datasets for any watershed of interest in the contiguous United States. The datasets are saved to a local geodatabase, and spatial operations are executed to automatically delineate the watershed, derive topological connections, and estimate several common hydrologic parameters. An output basin text file is produced in HEC-HMS format for rapid model initialization. Highlights: A GIS tool rapidly preprocesses basin files for HEC-HMS hydrological modeling. The tool can streamline common geospatial steps for other hydrological applications. The Living Atlas map service provides authoritative data in a useful GIS format. Improved accessibility to data services enhances standard GIS-based hydrology.